2002
DOI: 10.1128/jcm.40.8.2832-2836.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage of Potential Bacterial Pathogens Related to Day Care Attendance, with Special Reference to the Molecular Epidemiology of Haemophilus influenzae

Abstract: Nasopharyngeal carriage of Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis was studied in 259 children attending day care centers (DCC) in Amsterdam, The Netherlands, and in 276 control children. The DCC children were sampled a second time after 4 weeks. Carriage rates for DCC children and controls were 58 and 37% for S. pneumoniae, 37 and 11% for H. influenzae, and 80 and 48% for M. catarrhalis, respectively. No increased antibiotic resistance rates were found in strains isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 25 publications
4
65
1
Order By: Relevance
“…The most common bacterial species cultured from the nasopharynx of children during otitis media episodes are Streptococcus pneumoniae, Haemophilus influenzae, M. catarrhalis and Staphylococcus aureus, either as single pathogens or as co-cultures (Berner et al, 1996;Pettigrew et al, 2008), with the patterns of nasopharyngeal colonization by micro-organisms being important determinants for otitis media disease (Faden et al, 1991(Faden et al, , 1997Murphy & Parameswaran, 2009). With respect to M. catarrhalis, it has been shown that many factors affect nasopharyngeal carriage of this human-specific pathogen, including, for example, the presence of siblings, day care attendance and respiratory illness (Faden et al, 1997;Hendley et al, 2005;Peerbooms et al, 2002;Principi et al, 1999;Verhaegh et al, 2010). Furthermore, there is increasing information regarding the biological mechanisms facilitating M. catarrhalis-mediated colonization and disease development, with most publications stressing the importance of bacterial adherence as an essential first step in this process.…”
mentioning
confidence: 99%
“…The most common bacterial species cultured from the nasopharynx of children during otitis media episodes are Streptococcus pneumoniae, Haemophilus influenzae, M. catarrhalis and Staphylococcus aureus, either as single pathogens or as co-cultures (Berner et al, 1996;Pettigrew et al, 2008), with the patterns of nasopharyngeal colonization by micro-organisms being important determinants for otitis media disease (Faden et al, 1991(Faden et al, , 1997Murphy & Parameswaran, 2009). With respect to M. catarrhalis, it has been shown that many factors affect nasopharyngeal carriage of this human-specific pathogen, including, for example, the presence of siblings, day care attendance and respiratory illness (Faden et al, 1997;Hendley et al, 2005;Peerbooms et al, 2002;Principi et al, 1999;Verhaegh et al, 2010). Furthermore, there is increasing information regarding the biological mechanisms facilitating M. catarrhalis-mediated colonization and disease development, with most publications stressing the importance of bacterial adherence as an essential first step in this process.…”
mentioning
confidence: 99%
“…Although a high level of diversity has generally been found for NTHI, more frequent transmission of closely related strains among children living together in orphanages can support the idea of an association between transmission rates and environmental factors dependent on contact intensities. It seems that increased transmission rates and repeated passage through human hosts living more closely together might result in more 'clonal' relationships among isolates (Peerbooms et al, 2002). Larger numbers of isolates and institutions need to be compared in order to confirm or reject this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…66 Results from a northern Indian study, a of humans and is transmitted via respiratory secretions. 25 Most commonly commensal of the nasopharynx, especially in young children, 24,[26][27][28][29][30][31][32][33][34][35][36] although it is also found in the oropharynx. 19,[37][38][39][40][41] The detection of Hib is determined by microbiological culture.…”
Section: Risks Associated With Hib Carriagementioning
confidence: 99%
“…This social and demographic risk, has been associated with increases Hib carriage and for this reason, these centers are often targeted for routine surveillance of Hib carriage and other childhood pathogens. 21,33,38,70,71,73,[80][81][82][83][84][85][86][87] Special efforts to immunize children attending day-care centers need to be continually emphasized as this poses a higher risk to Hib than for children who do not attend day-care.…”
Section: Risks Associated With Hib Carriagementioning
confidence: 99%